Polyvinylpyrrolidone as a new fluorescent sensor for nitrate ion - Tang, Ing Hua (Malaysian Society of Analytical Sciences, 2016)
In this study, non-conjugated polyvinylpyrrolidone(PVP) was investigated for the first time as the potential polymeric material to sense nitrate ions by fluorescence spectroscopy. The PVP was diluted into various concentrations (3-10%) and they were used to sense the nitrate ions in different concentrations (0.1-100 mM). The PVP showed two excitation peaks at 285 and 330 nm due to the presence of C=O and N-C groups, respectively. One strong emission at 400 or 408 nm was observed with the excitation at 285 or 330 nm. The higher value of quenching constant at excitation wavelength of 285 nm indicated that C=O site was more favored for NO3- ions sensing than the N-C site. The PVP 7% gave the highest quenching constant; where the KSV value was 9.89 × 10-3 mM-1 and 2.44 × 10-3 mM-1 for excitation at 285 and 330 nm, respectively. The sensing capability was evaluated in the presence of interference ions (SO42-, HCO3-, Cl-, and OH-). It was observed that the interference ions interacted strongly with the C=O, but weakly with the N-C. Therefore, in the presence of the interference ions, the PVP would be a potential fluorescent sensor when it is excited at 330 nm.